A case of maxillary sarcoma in a chimpanzee (Pan troglodytes). Issue 2 (5th December 2013) - Fujisawa, M.; Udono, T.; Nogami, E.; Hirosawa, M.; Morimura, N.; Saito, A.; Seres, M.; Teramoto, M.; Nagano, K.; Mori, Y.; Uesaka, H.; Nasu, K.; et al.
Abstract Oral malignancy is rare in chimpanzees. A 34‐year‐old female chimpanzee (Pan troglodytes) at Kumamoto Sanctuary, Japan, had developed it. Treatment is technically difficult for chimpanzees while malignant neoplasm is seemingly rising in captive populations. Widespread expert discussion, guidelines for treatment, especially for great apes in terminal stages is urgently needed.